Aptitudes de aprendizaje y desempeño escolar en niños y jóvenes con epilepsia ausencia (2015)
Introduction: Although cognitive and learning disorders have been described in patients with epilepsy, very few studies focus on specific disorders such as absence epilepsy. The aim of this study was to evaluate learning skills and academic performance in children and adolescents with absence epilepsy. Methods: Observational case-control study. Cases were chosen from the Central League against Epilepsy's clinic in Bogotá, Colombia. Controls were selected from a private school and matched with cases by age, school year, and sex. Medical history, seizure frequency, antiepileptic treatment, and academic performance were assessed. Academic abilities were tested with Batería de Aptitudes Diferenciales y Generales (BADyG) (a Spanish-language test of differential and general aptitudes). Data were analysed using Student t-test. Results: The sample consisted of 19 cases and 19 controls aged between 7 and 16. In 15 patients, seizures were controlled; all patients had received antiepileptic medication at some point and 78.9% were actively being treated. Although cases had higher rates of academic failure, a greater incidence of grade retention, and more therapeutic interventions than controls, these differences were not significant. Similarly, there were no significant differences on the BADyG test, except for the immediate memory subcategory on which cases scored higher than controls (P=.0006). Conclusion: Children treated pharmacologically for absence epilepsy, whose seizures are controlled, have normal academic abilities and skills for their age. © 2013 Sociedad Española de Neurología.